Pemenuhan Kebutuhan Kasih Sayang Lansia UPT PSLU Blitar di Tulungagung - Mochamad Shofaul Qulub (STIKes Patria Husada Blitar, 2014)
Love and belonging is one of the needs in the Maslow hierarchy. Â Elders felt lonely when peoples at home busy at work and spending much time outdoor. Although every needed fulfill but elders felt lost of love and belonging from their family. The purpose of this study wasÂ determine love and belonging needs of elders in UPT PSLU Blitar in Tuluangagung by 4 parameters there are: communication with positive feelings, respect each other a happy business, providing the opportunity or freedom, and self-control or attention. Method: Research design was descriptive design. Research sample was 44 by using purposive sampling. Data collected Â on March to May 2014 by questionnaires love and belonging needs of elders. Results: The result showed that good love and belonging fulfillment 70.5% (31 elders), the fulfillment of the needs love and belonging enough about 27.3% (12 elders), and 2.3% (1 elders) needs less fulfilled. Discuss: Based of this study are expected to provide optimal services to the elders at UPT.PSLU Blitar in Tulungagung specially for elders who have less of love and belonging fulfilled.